Why have a bottle when you can have draught? Exploring bottle refusal by breastfed babies - Clare Maxwell; Valerie Fleming; Lorna Porcellato (Maternal and Child Nutrition, 2023)
Abstract Bottle refusal by breastfed babies is a scenario that has received surprisingly little attention in the literature, given the number of mothers who appear to be experiencing it globally and the subsequent negative impact it can have. In line with this, we undertook a study to explore mothers’ views on why their breastfed baby refuses to bottle feed. A parallel, two‐stage, exploratory qualitative design was employed using 30 semi‐structured interviews and 597 online forum posts. Data were analysed using a thematic analysis, and a biopsychosocial model was applied resulting in four overarching themes being identified: ‘Breastfeeding is the answer to everything….’ ‘Bottle feeding: an alien concept… ‘Babies are individuals’ and ‘Find the right bottle and don't delay’. The psychological benefits of breastfeeding, not inherent in bottle feeding, appeared to underpin some mothers’ views on their baby's refusal. Other mothers explained refusal as being down to a baby's biological expectation to be fed by the breast; therefore, bottle feeding was not a normal concept to them. A baby's individual personality and temperament were also suggested as contributing to the scenario and refusal was linked to babies disliking a certain brand of bottle and being introduced to it ‘too late’. This study's findings point to a complex, multifactorial picture underpinning bottle refusal by breastfed babies, which transcends physical, psychological and biological concepts, and is influenced by socio‐cultural norms surrounding infant feeding. Recognition of these contributing factors is needed to aid those supporting mothers experiencing the scenario and, importantly, to underpin mothers’ decision‐making around managing it.